Copper(II) complexes of cyclams with N-(2,2,2-trifluoroethyl)-aminoalkyl pendant arms as potential probes for 19F magnetic resonance imaging - Kotková, Zuzana; Koucký, Filip; Kotek, Jan; Císařová, Ivana; Parker, David; Hermann, Petr (Dalton transactions (Cambridge, England, 2023)
A series of Cu(II) complexes with cyclam-based ligands containing two N-(2,2,2-trifluoroethyl)-aminoalkyl pendant arms in 1,8-positions (L1: 1,2-ethylene spacer, L2: 1,3-propylene spacer; L3: 1,4-butylene spacer) was studied in respect to potential use as contrast agents for 19F magnetic resonance imaging (MRI). A number of structures of the complexes as well as of several organic precursors were determined by single-crystal X-ray diffraction analysis. Geometric parameters (especially distances between fluorine atoms and the central metal ion) were determined for each complex and the identity of isomeric complex species present in solution was established. The NMR longitudinal relaxation times (T1) of 19F nuclei in the ligands at clinically relevant fields and temperatures (1-2 s) were significantly shortened upon Cu(II) binding to 7-10 ms for [Cu(L1)]2+, 20-30 ms for [Cu(L2)]2+ and 20-50 ms for [Cu(L3)]2+. The trend of the relaxation time shortening is in accordance with the distance and number of chemical bonds between fluorine atoms and the Cu(II) ion. The signals show promising T2*/T1 ratios in the range 0.25-0.55, assuring their good applicability to 19F NMR/MRI. The results show that even the Cu(II) ion, with a small magnetic moment, causes significant relaxation enhancement with a long-range effect and can be considered as a highly suitable metal ion for efficient 19F MRI contrast agents.